(3GdeHgL aj GdbQGAGJ GdSHYIs - (3CHh eMeO YHO Gddg Hf Ydj Hf CMeO Hf YHO Gddg, SHW GdNjGW GdHZOGOj,J (B541 (3g` s ((3GdeUfa s)
(3ChdgG (B:s
(3GdMeO ddg Pi GdfYe GdLSjeI CeG HYO aEfi eYhd Ydi LeY cJGH jTJed Ydi bQGAI GdCFeI GdSHYI s
(3BNQgG (B:s
(3jG eYHO GdCQhGM Edi CLdgG jZjQ YOegG hLGeY eG gQb aef QeegG Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3eJaQbGJs